42 (a _4 - 13 a_3 + 36a _2 )by 7a (a-4 )
Answers
Answered by
3
Hey friend, Harish here.
Here is your answer:
To find:
![\frac{42(a ^{4} - 13 a^{3} + 36a ^{2}) }{7a(a-4)} \frac{42(a ^{4} - 13 a^{3} + 36a ^{2}) }{7a(a-4)}](https://tex.z-dn.net/?f=+%5Cfrac%7B42%28a+%5E%7B4%7D+-+13+a%5E%7B3%7D+%2B+36a+%5E%7B2%7D%29+%7D%7B7a%28a-4%29%7D+)
Solution:
Now in the numerator take a² as common.
Then,
![\frac{42a^{2}(a^{2} - 13 a + 36)}{7a(a-4)} \frac{42a^{2}(a^{2} - 13 a + 36)}{7a(a-4)}](https://tex.z-dn.net/?f=+%5Cfrac%7B42a%5E%7B2%7D%28a%5E%7B2%7D+-+13+a+%2B+36%29%7D%7B7a%28a-4%29%7D++)
![\frac{42a^{2}}{7a} \times ( \frac{(a^{2} - 13 a + 36)}{(a-4)}) \frac{42a^{2}}{7a} \times ( \frac{(a^{2} - 13 a + 36)}{(a-4)})](https://tex.z-dn.net/?f=+%5Cfrac%7B42a%5E%7B2%7D%7D%7B7a%7D+%5Ctimes+%28+%5Cfrac%7B%28a%5E%7B2%7D+-+13+a+%2B+36%29%7D%7B%28a-4%29%7D%29+++)
Now , We know that, 42/7 = 6. and a² & a get canceled.
Then,
![6a \times ( \frac{(a^{2} - 13 a + 36)}{(a-4)}) 6a \times ( \frac{(a^{2} - 13 a + 36)}{(a-4)})](https://tex.z-dn.net/?f=6a+%5Ctimes+%28+%5Cfrac%7B%28a%5E%7B2%7D+-+13+a+%2B+36%29%7D%7B%28a-4%29%7D%29+)
Now factorize the numerator using splitting the middle term:
Then,
⇒![6a \times( \frac{(a^{2} - 13 a + 36)}{(a-4)}) = 6a\times ( \frac{((a^{2} - 4 a -9a+ 36))}{(a-4)}) 6a \times( \frac{(a^{2} - 13 a + 36)}{(a-4)}) = 6a\times ( \frac{((a^{2} - 4 a -9a+ 36))}{(a-4)})](https://tex.z-dn.net/?f=6a+%5Ctimes%28+%5Cfrac%7B%28a%5E%7B2%7D+-+13+a+%2B+36%29%7D%7B%28a-4%29%7D%29+%3D+6a%5Ctimes++%28+%5Cfrac%7B%28%28a%5E%7B2%7D+-+4+a+-9a%2B+36%29%29%7D%7B%28a-4%29%7D%29++)
⇒![6a \times ( \frac{a(a - 4)-9(a-4))}{(a-4)}=6a\times \frac{(a-4)(a-9)}{(a-4)} 6a \times ( \frac{a(a - 4)-9(a-4))}{(a-4)}=6a\times \frac{(a-4)(a-9)}{(a-4)}](https://tex.z-dn.net/?f=6a+%5Ctimes+%28+%5Cfrac%7Ba%28a+-+4%29-9%28a-4%29%29%7D%7B%28a-4%29%7D%3D6a%5Ctimes++%5Cfrac%7B%28a-4%29%28a-9%29%7D%7B%28a-4%29%7D++)
Now, We can cancel (a-4) & (a-4).
Then,
⇒![6a\times \frac{(a-4)(a-9)}{(a-4)} = 6a \times (a-9) 6a\times \frac{(a-4)(a-9)}{(a-4)} = 6a \times (a-9)](https://tex.z-dn.net/?f=6a%5Ctimes+%5Cfrac%7B%28a-4%29%28a-9%29%7D%7B%28a-4%29%7D++%3D+6a+%5Ctimes+%28a-9%29)
⇒![6a^{2} - 54a 6a^{2} - 54a](https://tex.z-dn.net/?f=6a%5E%7B2%7D+-+54a)
Therefore the answer is 6a² - 54a.
________________________________________________
Hope my answer is helpful to you.
Here is your answer:
To find:
Solution:
Now in the numerator take a² as common.
Then,
Now , We know that, 42/7 = 6. and a² & a get canceled.
Then,
Now factorize the numerator using splitting the middle term:
Then,
⇒
⇒
Now, We can cancel (a-4) & (a-4).
Then,
⇒
⇒
Therefore the answer is 6a² - 54a.
________________________________________________
Hope my answer is helpful to you.
HarishAS:
Any doubts?
Similar questions